Pleural solitary fibrous tumour with brain metastasis: an aggressive tumour and pathologic conundrum. Issue 8 (4th August 2022) - Williams, Catherine; French, Daniel; Christie, Sean; Castonguay, Mathieu; Wallace, Alison
Abstract: Solitary fibrous tumours of the pleura are a rare finding; those with brain metastases are rarer still. Here, we present the evolution of a pleural solitary fibrous tumour in a 70-year-old male treated surgically, and subsequent brain metastasis requiring emergent craniotomy and excision. The patient received adjuvant radiotherapy to the brain and had no recurrence of brain metastases; however, 1 year surveillance imaging demonstrated metastases to the lungs, liver and spleen for which he received chemotherapy but eventually succumbed to the disease process. Solitary fibrous tumours are most often slow-growing, relatively benign neoplasms. However, up to 10% are malignant. This case highlights the importance of surgical resection of these benign tumours with malignant potential.